Cheap zeolite catalyst (Na3PO4/NaX) for toluene/methanol side chain alkylation - Ahmad, Faraz; Wen, Yueli; Wang, Bin; Hao, Chunyao; Yousaf, Walzli; Liu, Yuhua; Huang, Wei (International Journal of Advanced Engineering Research and Science, 2020)
A new zeolite catalyst (Na3PO4/NaX), which is low in cost, environment-friendly and also gives higher conversion of methanol, was prepared by the impregnation method and catalytic performance was tested for side-chain alkylation of toluene with methanol. From the characterization of the catalysts by Temperature-programmed desorption (TPD-CO2), X-ray diffraction (XRD), scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET) method we found that when the concentration of Na3PO4 was 0.1 mol/L, the yield of styrene and ethylbenzene, and conversion of methanol reached 39.4% and 100%. It was determined that as the loading of Na3PO4 onto the NaX surface enhanced, the amount and the strength of middle base sites significantly increased, which is favorable for the toluene/methanol side chain alkylation.